Chatbots — an organisation's friend or foe?. Issue 2 (3rd July 2019) - Carter, Emma; Knol, Charlotte
ABSTRACT: In recent years, the use of artificial intelligence has increased tremendously and the hospitality industry has not gone unaffected. Nowadays, chatbots, which simulate human conversations, are almost indispensable in the customer service branch of hospitality. Where organisations started rapidly with the introduction of this new technology, they are now raising the question of whether or not this technological evolution is a good development for this industry. On the one hand, chatbots improve and accelerate customer service, saving time and labour costs. On the other hand, there are privacy and security concerns, lack of personality and lack of research resulting in errors and financial expenses. Presently, chatbots are seen as a technology to support human service, but due to rapid development this situation is open to change.